Desain dan Analisis Kekuatan Rangka Mesin Pres Batako Menggunakan Finite Element Method: Design and Strength Analysis of Brick Press Machine Frame using Finite Element Method - Anggi Pratama; Delvis Agusman (Fakultas Teknik Universitas Pancasila, 2023)
This study investigates the safety factor and stress in order to determine the utmost dynamic load the press machine frame can withstand. Dynamic loads occur because of the working mechanism of the press machine, which suppresses the brick components. Test simulation stress analysis using the computer program Inventor Professional Student 2023 with the finite element method in a material structure simulation test of a brick press machine frame with a dynamic load treatment the frame design model uses mild steel material with dimensions of 880 mm by 545 mm by 1200 mm. The variable loads are 700 kg, 1000 kg, and 1500kg. The simulation results show the displacement value at a load of 700 kg = 0,25 mm; 1000 kg = 0,36 mm; and 1500 kg = 0,54 mm. The von Mises stress value is 700 kg = 70,03 MPa; 1000 kg = 100,4 MPa; and 1500 kg = 150,9 MPa. The safety factor value is 700 kg = 2,96; 1000 kg = 2,06; and 1500 kg = 1,37. The simulation results show that the frame design of the brick press machine has a safety factor of 2,06 and can withstand a dynamic load of up to 1000 kg.